Dictionarium museologicum = Dictionary of museology - Éri, István, 1929-2009; Végh, Béla (Hungarian Esperanto Association, 1986)
Dictionary of museological terms in twenty languages (english, french, spanish, russian, german, bulgarian, czech, danish, esperanto, finnish, hungarian, italian, dutch, norwegian, polish, portuguese, rumanian, serbo-croatian, slovak, swedish). Appendices: lists of special terms with no english-entry equivalents and list of national and international museum organizations, institutions and societies.